Chiridota heheva, new species, from Western Atlantic deep-sea cold seeps and anthropogenic habitats (Echinodermata: Holothuroidea: Apodida) - Pawson, David L.; Vance, Doris J. (Zootaxa, 2004)
Chiridota heheva new species is described from cold seeps off Georgia and Florida, a shipwreck off Georgia, and an artificial wood-block habitat near Puerto Rico, in bathyal-abyssal depths of 2,200 3,300 meters. C. heheva is similar in some respects to C. hydrothermica Smirnov & Gebruk from Western and Southeastern Pacific hydrothermal vents, but it differs in structure of the tentacles and in color.